PENGARUH KOMPOSISI MEDIA TANAM DAN KONSENTRASI PUPUK DAUN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) - Endra Syahputra; Marai Rahmawati; Said Imran (Jurnal Floratek, 2014)
This study was aimed at determining the appropriate growing medium composition and foliar fertilizer concentration and their interaction on growth and yield of lettuce. The experiment was arranged in a randomized complete block design (RCBD), consisting of two factors, i.e. the growing media composition and foliar fertilizer concentration. The first factor consisted of the composition of the soil and manure by volume ratio (3:1, 3:2, and 3:3) and the second factor consisted of foliar fertilizer concentrations (0, 2, 4 mL/L of water ). The results showed that the growing media composition soil+manure (3:3) was the best in increasing crop height, leaves number, leaf length, leaf width and yield at 35 day after planting, while the best concentration for those parameters was 4 mL/L of water. Based on the interaction, the best leaf number of lettuce was found at growing media composition soil+manure (3:3) with the concentration of foliar fertilizer 4 mL/L of water.